Determinants Affecting the Dental Care Decision at Dental Clinics in Bandung - Yogi Suprayogi; Ratih Hurriyati; Puspo Dewi Dirgantari; Nurul Hutami Ningsih (Jurnal Manajemen Indonesia, 2022)
The business development of dental clinics in the city of Bandung is growing rapidly along with public awareness of the importance of dental health. There has been a decrease in income at dental clinics in Bandung due to the pandemic in the last two years and similar business competition, so researchers want to help and find out what variables influence people's decisions in choosing a dental clinic. This research aimed at examining the effect of sales promotion, lifestyle, and price discount variables on dental care decisions at dental clinics in Bandung. The data were taken from 105 respondents who had experience having dental care at the dental clinics in Bandung by using online questionnaires. The analysis technique used multiple linear regression. The results showed that there was an influence of sales promotion, lifestyle, and price discount variables if they were combined simultaneously, on dental care decisions at the dental clinic in Bandung, but if it was seen partially, the price discount variable did not affect the decision to have dental care at dental clinics in Bandung. This research also proved that sales promotion and lifestyle had a positive and significant impact on dental treatment decisions at dental clinics in Bandung. The findings were further discussed in this research. Keywords—sales promotion; lifestyle; price discount; purchasing decision; dental clinics.